Corrosion behaviors of low‐temperature plasma nickelized coatings on titanium alloy. Issue 12 (6th September 2016) - Fu, T.‐L.; Zhan, Z.‐L.; Zhang, L.; Yang, Y.‐R.; Liu, Z.; Liu, J.‐X.
Abstract : A Ni coating was prepared on a titanium alloy by plasma nickelizing, at a low temperature of 450 °C, after a surface mechanical attrition treatment. This coating consisted of Ni3 Ti and NiTi phases. Polarization curves, open circuit potential, and electrochemical impedance spectroscopy measurements were used to evaluate the corrosion behavior of the coatings. These measurements revealed the improved corrosion behavior of the samples after the nickelized SMAT Ti process. The oxide films formed on the coating were characterized via X‐ray photoelectron spectroscopy. The complex titanium and nickel oxides provided excellent corrosion resistance to the 3.5% NaCl solution. Abstract : A Ni coating was prepared on a titanium alloy by plasma nickelizing, at a low temperature of 450 °C, after a surface mechanical attrition treatment. This coating consisted of Ni3 Ti and NiTi phases. Polarization curves, open circuit potential, and EIS measurements revealed the improved corrosion behavior of the samples after the nickelized SMAT Ti process.